2014
DOI: 10.1007/s00792-014-0693-2
|View full text |Cite
|
Sign up to set email alerts
|

Extremely ‘vanadiphilic’ multiply metal-resistant and halophilic aerobic anoxygenic phototrophs, strains EG13 and EG8, from hypersaline springs in Canada

Abstract: Two pinkish peach-colored strains of obligately aerobic phototrophic bacteria, EG13 and EG8, were isolated from a saline spring effluent stream in west central Manitoba, Canada. The strains possessed bacteriochlorophyll a incorporated into a typical purple bacterial light-harvesting complex 1 (870 nm) and reaction center (801 nm). Analysis of 16S rRNA gene sequences indicated 100% identity among the isolates and 99% similarity to Roseovarius tolerans EL-172(T). The strains were physiologically well adapted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…previously reported for aerobic anoxygenic phototrophs for vanadate [45] and tellurite [46], where metal(loid) oxides are potentially acting in catalytic electron shuttling, promoting energy production and faster growth for the bacterium under those conditions. A comparison of unique PGFams from the genome of ER-Te-42B-Light T versus the five closest relatives revealed 53 unique protein families in the new strain not found elsewhere (Table S4).…”
Section: Resultsmentioning
confidence: 81%
“…previously reported for aerobic anoxygenic phototrophs for vanadate [45] and tellurite [46], where metal(loid) oxides are potentially acting in catalytic electron shuttling, promoting energy production and faster growth for the bacterium under those conditions. A comparison of unique PGFams from the genome of ER-Te-42B-Light T versus the five closest relatives revealed 53 unique protein families in the new strain not found elsewhere (Table S4).…”
Section: Resultsmentioning
confidence: 81%
“…The results of molecular identification sho- (Lin, 2018) Bacillus anthracis strain WY2 KF641920.1 (Chun et al, 2012) Bacillus aryabhattai strain APBSWPTB141 MG733614.1 (Krishnamoorthy & Gunthe, 2017) Bacillus cereus strain SWFU2816 JN935015.1 (Wang & Zhang, 2011) Clostridium botulinum strain CIFT_Mfb_julcb8 MG793684.1 (Athira et al, 2017) Clostridium sporogenes strain LAG1 MH760799.1 (Awotula et al, 2018) Cronobacter sakazakii strain 1 KY524290.1 (Gabra, 2017) Enterobacter cloacae strain PB-S2 GU459209.1 (Beneduzi et al, 2008) Enterobacter tabaci strain BC2505 MF682952.1 (Bae et al, 2018) Escherichia vulneris strain NEW-ERY-1 MF079358.1 (Han, 2018) Klebsiella pneumoniae strain KP7 MH819550.1 (Baqer, 2018) Shigella sonnei strain E10 MH174662.1 (Hajoori & Jain, 2018) Sporomusa malonica strain DSM 5090 NR_117652.1 (Csotonyi et al, 2015) Sporomusa rhizae strain RS NR_042457.1 (Gößner et al, 2006) Xenorhabdus sp. PDBC SCX7 1 DQ026512.1 (Nagesh et al, 2005) of the main groups.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this increase is unclear, however, there is precedent, as the bacterium strain EG13 also has increased biomass production (4.5 fold) in the presence of other metalloid oxyanions (NaVO 3 ) compared to metal free medium [ 45 ]. It has been suggested that reduction of metal(loid) oxyanions can help dispose of excess electrons through the reoxidation of NADH, FADH 2 , or quinones, therefore retaining optimal redox poise in vivo [ 16 , 45 , 46 ]. This may result in optimal conditions for growth being maintained longer than in the absence of the oxyanion.…”
Section: Discussionmentioning
confidence: 99%